Effects of Photoperiod on Epididymal and Sperm Morphology in a Wild Rodent, the Viscacha (Lagostomus maximus maximus). (2nd December 2012) - Cruceño, A. M.; de Rosas, J. C.; Fóscolo, M.; Chaves, E. M.; Scardapane, L.; Dominguez, S.; Aguilera-Merlo, C.
Abstract : The viscacha ( Lagostomus maximus maximus ) is a seasonal South American wild rodent. The adult males exhibit an annual reproductive cycle with periods of maximum and minimum gonadal activity. Four segments have been identified in the epididymis of this species: initial, caput, corpus, and cauda. The main objective of this work was to relate the seasonal morphological changes observed in the epididymal duct with the data from epididymal sperm during periods of activity and gonadal regression using light and scanning electron microscopy (SEM). Under light and electron microscopy, epididymal corpus and cauda showed marked seasonal variations in structural parameters and in the distribution of different cellular populations of epithelium. Initial and caput segments showed mild morphological variations between the two periods. Changes in epididymal sperm morphology were observed in the periods analyzed and an increased number of abnormal gametes were found during the regression period. During this period, anomalies were found mainly in the head, midpiece, and neck, while in the activity period, defects were found only in the head. Our results confirm that the morphological characteristics of the epididymal segments, as well as sperm morphology, undergo significant changes during the reproductive cycle of Lagostomus .